Review: nutritional and endocrine control of colostrogenesis in swine. (July 2019) - Quesnel, H.; Farmer, C.
Abstract : Colostrum plays an essential role in ensuring the survival, growth and health of piglets by providing energy, nutrients, immunoglobulins, growth factors and many other bioactive components and cells. Both colostrum yield and composition are highly variable among sows, yet mechanisms and factors that regulate colostrogenesis are not fully known. Unlike sow milk yield, sow colostrum yield is not highly determined by litter size and suckling intensity but is largely driven by sow-related factors. Colostrum synthesis is under hormonal control, with prolactin and progesterone concentrations prepartum having, respectively, positive and negative influences on colostrum yield. Less is known about the endocrine control of the end of colostrogenesis in swine, which is characterized by the closure of tight junctions in the mammary epithelium and the cessation of transfer of immunoglobulin G (IgG) into lacteal secretions. Recent studies indicate that exogenous hormones may influence colostrogenesis. Inducing parturition by injecting prostaglandin F2 α on day 114 of gestation in combination with an oxytocin-like molecule reduced colostrum yield, and injection of prostaglandin F2 α alone either reduced colostrum yield or had no effect. Injecting a supraphysiological dose of oxytocin to sows in the early postpartum period delayed the tightening of mammary tight junctions, thereby prolonging the colostral phase and increasing concentrations of IGF-I and IgG and IgA in early milk. The development of strategies to improve colostrum composition in swine through maternal feeding has been largely explored but very few attempts were made to increase colostrum yield. This is most likely because of the difficulty in measuring colostrum yield in swine. The fatty acid content of colostrum greatly depends on the amount of lipids provided in the sow diet during late gestation, whereas the fatty acid profile is largely influenced by the type of lipid being fed to the pregnant sow. Moreover, various ingredients that presumably have immuno-modulating effects (such as fish oil, prebiotics and probiotics) increased concentrations of IgG, IgA and/or IgM in sow colostrum when they were provided during the last weeks of gestation. Finally, there is some evidence that sow nutrition during late gestation may influence colostrum yield but this clearly warrants more research. This review emphasizes that although progress has been made in understanding the control of colostrogenesis in swine, and that strategies exist to manipulate fat and immunoglobulin contents of colostrum, ways to increase colostrum yield are still lacking.